Asymmetry in genitalia is in sync with lateralized mating behavior but not with the lateralization of other behaviors - Torres Dowdall, Julián Roberto (2019)
Asymmetries in bilateral organisms attract a lot of curiosity given that they are conspicuous departures from the norm. They allow the investigation of the integration at different levels of biological organization. Here we study whether and how behavioral and asymmetrical anatomical traits co-evolved and work together. We ask if asymmetry is determined locally for each trait or at a whole individual level in a species bearing conspicuous asymmetrical genitalia. Asymmetric genitalia evolved in many species; however, in most cases the direction of asymmetry is fixed. Therefore, it has been rarely determined if there is an association between the direction of asymmetry in genitalia and other traits. In onesided livebearer fish of the genus Jenynsia (Cyprinodontiformes, Anablepidae), the anal fin of males is modified into a gonopodium, an intromittent organ that serves to inseminate females. The gonopodium shows a conspicuous asymmetry, with its tip bending either to the left or the right. By surveying 13 natural populations of Jenynsia lineata, we found that both genital morphs are equally common in wild populations. In a series of experiments in a laboratory population, we discovered asymmetry and lateralization for multiple other traits; yet, the degree of integration varied highly among them. Lateralization in exploratory behavior in response to different stimuli was not associated with genital morphology. Interestingly, the direction of genital asymmetry was positively correlated with sidedness of mating preference and the number of neuromasts in the lateral line. This suggests integration of functionally linked asymmetric traits; however, there is no evidence that asymmetry is determined at the whole individual level in our study species.